The impact of COVID-19 on neurosurgeons and the strategy for triaging non-emergent operations: a global neurosurgery study - Jean, Walter C. (Acta Neurochir (Wien), 2020)
OBJECT: The COVID-19 pandemic has disrupted all aspects of society globally. As healthcare resources had to be preserved for infected patients, and the risk of in-hospital procedures escalated for uninfected patients and staff, neurosurgeons around the world have had to postpone non-emergent procedures. Under these unprecedented conditions, the decision to defer cases became increasingly difficult as COVID-19 cases skyrocketed. METHODS: Data was collected by self-reporting surveys during two discrete periods: the principal survey accrued responses during 2 weeks at the peak of the global pandemic, and the supplemental survey accrued responses after that to detect changes in opinions and circumstances. Nine hypothetical surgical scenarios were used to query neurosurgeons’ opinion on the risk of postponement and the urgency to re-schedule the procedures. An acuity index was generated for each scenario, and this was used to rank the nine cases. RESULTS: There were 494 respondents to the principal survey from 60 countries. 258 (52.5%) reported that all elective cases and clinics have been shut down by their main hospital. A total of 226 respondents (46.1%) reported that their operative volume had dropped more than 50%. For the countries most affected by COVID-19, this proportion was 54.7%. There was a high degree of agreement among our respondents that fast-evolving neuro-oncological cases are non-emergent cases that nonetheless have the highest risk in postponement, and selected vascular cases may have high acuity as well. CONCLUSION: We report on the impact of COVID-19 on neurosurgeons around the world. From their ranking of the nine case scenarios, we deduced a strategic scheme that can serve as a guideline to triage non-emergent neurosurgical procedures during the pandemic. With it, hopefully, neurosurgeons can continue to serve their patients without endangering them either neurologically or risking their exposure to the deadly virus. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00701-020-04342-5) contains supplementary material, which is available to authorized users.